Pencegahan Catheter Associated Urinary Tractus Infection Melalui Catheter Maintenance - Waluyo Waluyo; Kusnanto Kusnanto; Yanis Kartini (FORIKES, 2020)
Catheter associated urinary tractus infection is a urinary tract infection due to urinary catheter placement that lasts more than two days. Catheter associated urinary tractus infection can be prevented by applying infection prevention practices based on proven evidence. Catheter maintenance are some of the measures to prevent the infection. Nurse compliance with catheter care and catheter maintenance is very important in preventing catheter associated urinary tractus infection. The aims of this study was to determine the increase in prevention of catheter associated urinary tractus infection by training catheter maintenance. This research was an experimental using a one-group pre-post test design. The study population consisted of inpatient nurses by 51 nurses and 116 patients with permanent urinary catheters. The technique of sampling used total sampling. Data analysis performed with a Wilcoxon signed rank test test. The result of wilcoxon test showed the p value of signature of 0.00 so that there was an influence between training on catheter maintenance on increasing the prevention of catheter associated urinary tractus infection. The result of training catheter maintenance was to increase nurse compliance in preventing catheter associated urinary tractus infection. Keywords: catheter maintenance; urinary tractus infection ABSTRAK Catheter Associated Urinary Tractus Infection merupakan infeksi saluran kemih akibat pemasangan kateter urin yang menetap lebih dari dua hari. Catheter associated urinary tractus infection dapat dicegah dengan cara menerapkan praktik pencegahan infeksi berdasarkan bukti yang sudah teruji. Catheter maintenance merupakan sebagian dari beberapa tindakan untuk mencegah infeksi tersebut. Kepatuhan perawat terhadap pelaksanaan catheter maintenance sangat penting dalam mencegah catheter associated urinary tractus infection ini. Tujuan penelitian ini adalah untuk mengetahui peningkatan pencegahan catheter associated urinary tractus infection dengan pelatihan catheter maintenance. Penelitian ini merupakan quasi eksperiment dengan menggunakan rancangan one-group pre-post test design. Populasi penelitian ini perawat ruang rawat inap sebesar 51 perawat dan 116 pasien yang terpasang kateter urin menetap. Tehnik sampling yang digunakan adalah total sampling. Analisis data dilakukan dengan uji statistik Wilcoxon signed rank test dengan hasil p value signifikansi 0,00 sehingga ada ada pengaruh antara pelatihan tentang catheter maintenance terhadap peningkatan pencegahan catheter associated urinary tractus infection. Hasil dalam penelitian ini adalah pelatihan catheter maintenance meningkatkan kepatuhan perawat dalam pencegahan catheter associated urinary tractus infection. Kata kunci: catheter maintenance; urinary tractus infection